Epoxy Toughening with Low Graphene Loading. (6th December 2014) - Park, Yong Tae; Qian, Yuqiang; Chan, Clement; Suh, Taewon; Nejhad, Mehrdad Ghasemi; Macosko, Christopher W.; Stein, Andreas
<x xml:space="preserve">Abstract</x> The toughening effects of graphene and graphene‐derived materials on thermosetting epoxies are investigated. Graphene materials with various structures and surface functional groups are incorporated into an epoxy resin by in situ polymerization. Graphene oxide (GO) and GO modified with amine‐terminated poly(butadiene‐acrylonitrile) (ATBN) are chosen to improve the dispersion of graphene nanosheets in epoxy and increase their interfacial adhesion. An impressive toughening effect is observed with less than 0.1 wt% graphene. A maximum in toughness at loadings as small as 0.02 wt% or 0.04 wt% is observed for all four types of graphene studied. An epoxy nanocomposite with ATBN‐modified GO shows a 1.5‐fold improvement in fracture toughness and a corresponding 2.4‐fold improvement in fracture energy at 0.04 wt% of graphene loading. At such low loadings, these graphene‐type materials become economically feasible components of nanocomposites. A microcrack mechanism is proposed based on microscopy of the fracture surfaces. Due to the stress concentration by graphene nanosheets, microcracks may be formed to absorb the fracture energy. However, above a certain graphene concentration, the coalescence of microcracks appears to facilitate crack propagation, lowering the fracture toughness. Crack deflection and pinning likely contribute to the slow increase in fracture toughness at higher loadings.